Towards standardized metrics for measuring takeover performance in conditionally automated driving: A systematic review. (September 2021) - Cao, Yining; Zhou, Feng; Pulver, Elizabeth M.; Molnar, Lisa J.; Robert, Lionel P.; Tilbury, Dawn M.; Yang, X. Jessie
A particular concern with SAE Level 3 automated vehicles is the takeover transition from the automated vehicle to the driver. Prior research has employed a wide range of metrics for measuring takeover performance. However, the lack of a set of standard metrics for measuring takeover performance makes it difficult to consolidate findings and summarize the influence of different factors. This article presents a review of the metrics employed in empirical literature examining takeover transitions in Level 3 automated driving and proposes a framework for standardizing the objective takeover performance metrics.